2010
DOI: 10.1111/j.1751-553x.2010.01234.x
|View full text |Cite
|
Sign up to set email alerts
|

An allelic typing method for 2DS4 variant used in study of haplotypes of killer cell immunoglobulin‐like receptor gene

Abstract: The KIR2DS4 variants differ in exon 5 and play a role in hematopoietic stem cells transplantation (HSCT). A sequence-based testing (SBT) and TOPO TA cloning system identifying and distinguishing alleles of the KIR2DS4 gene was established and applied to a total of 150 Chinese-Han individuals: 75 patients received T-cell-depleted HSCT and their unrelated donors. The majority (139) of the 150 samples (92.7%) were positive for KIR2DS4. Four of the nine known KIR2DS4 alleles, KIR2DS4 *00101, *003,*004, and *007, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…For 2DS3/S5 that can be located on both centrometric and telomeric sides, the gene was assigned basically on identified KIR gene motifs and the linkage between 2DL5A/B and 2DS3/S5 . In‐house locus specific primers were used to confirm the presence or absence of KIR3DS1 and deleted‐KIR2DS4 genes as there are occasionally weak PCR reactions for the corresponding wells using the commercial Kits .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For 2DS3/S5 that can be located on both centrometric and telomeric sides, the gene was assigned basically on identified KIR gene motifs and the linkage between 2DL5A/B and 2DS3/S5 . In‐house locus specific primers were used to confirm the presence or absence of KIR3DS1 and deleted‐KIR2DS4 genes as there are occasionally weak PCR reactions for the corresponding wells using the commercial Kits .…”
Section: Methodsmentioning
confidence: 99%
“…In humans, a unique feature of the KIR system is the segregation of two distinctive groups of haplotypes (A and B), which are present in all the >150 human populations examined and are maintained by balancing selection . Some recent studies have indicated that patients transplanted from donors carrying at least one B haplotype had a better clinical outcome compared with those transplanted from a donor homozygous for KIR haplotype A . These data highlight the effect of KIR haplotypes in allo‐HSCT.…”
Section: Introductionmentioning
confidence: 97%
“…(2004) showed that women who belong to haplotype A with a KIR1D may have less reproductive success. Bao et al. (2010) reported that more KIR1D allele in donor contributed to a lower risk of acute graft‐versus‐host disease in haplotype A group and led to a good clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the tumors with the highest incidence in China, the related research results show that (1) at present, the incidence of leukemia is increasing year by year (2). Currently, there is a high incidence of leukemia, especially acute leukemia, which is a cancer that progresses rapidly (3).…”
Section: Introductionmentioning
confidence: 99%